A Hypothesis: Hydrogen Sulfide Might Be Neuroprotective against Subarachnoid Hemorrhage Induced Brain Injury. (23rd February 2014) - Yu, Yong-Peng; Chi, Xiang-Lin; Liu, Li-Jun
Abstract : Gases such as nitric oxide (NO) and carbon monoxide (CO) play important roles both in normal physiology and in disease. Recent studies have shown that hydrogen sulfide (H2 S) protects neurons against oxidative stress and ischemia-reperfusion injury and attenuates lipopolysaccharides (LPS) induced neuroinflammation in microglia, exhibiting anti-inflammatory and antiapoptotic activities. The gas H2 S is emerging as a novel regulator of important physiologic functions such as arterial diameter, blood flow, and leukocyte adhesion. It has been known that multiple factors, including oxidative stress, free radicals, and neuronal nitric oxide synthesis as well as abnormal inflammatory responses, are involved in the mechanism underlying the brain injury after subarachnoid hemorrhage (SAH). Based on the multiple physiologic functions of H2 S, we speculate that it might be a promising, effective, and specific therapy for brain injury after SAH.